Assessing contributions of value-added medical student roles. (1st February 2021) - Gylys, Raymond; Rosenwohl-Mack, Sarah; Pierluissi, Edgar; Hoffman, Ari
Abstract: Value-added student roles—defined as student activities that simultaneously teach physicianship and improve the healthcare system—have rapidly gained popularity in recent years. Though many agree that value-added medical student roles can contribute both to student learning and to patient outcomes, impact evaluation of these roles can pose a challenge. In this Personal View, we describe our quality improvement project at UC San Francisco aimed at reducing unnecessary physical therapist (PT) referrals. While our primary outcome measure remained unchanged, the project helped to galvanize safe mobilization efforts in the hospital and led to the establishment of a UCSF Health Safe Mobilization Committee, leading to broader and potentially more impactful institutional systems changes. How do we interpret success, and how do we appraise the potential impact students can have in a complex health system? While we agree with the importance of process-focused metrics that assess student participation in an interprofessional, data-driven quality improvement effort, we also see a role for an expanded assessment of student contributions to capture systems improvements that may occur downstream of student activities.